Inventories–A Guide To Their Control, Costing and Effect Upon Income Taxes (Book). - Werntz, William W. (The Accounting Review, 1963)
Reviews the book "Inventories–A Guide To Their Control, Costing and Effect Upon Income Taxes," by Raymond A. Hoffman.